PENGARUH SELF CONFIDENCE TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIK SISWA SMP - Mentari Dini; Tommy Tanu Wijaya; Asep Ikin Sugandi (Universitas Muhammadiyah Ponorogo, 2018)
This study aims to analyze and examine in depth about student’s mathematics understanding ability influenced by self-confidence. The study was designed in the form of experiment using correlational method with quantitative appoach. The population in this research is junior high school student in Cimahi and the sample as many as 28 people determined by purposive sampling technique in one of junior high school in Cimahi. The instrument in the research is the test of mathematics understanding ability as much as 5 items and the scale of student’s self-confidence as much as 36 scale statment. Based on the results and discussion, it is concluded that the students’ mathematics understanding ability influenced positively by self-confidence equal to 74,6%, whilw 25,4% influenced by factors other than student self-confidence.